The Cyclical Adjustment Procedure of the German Debt Brake: a Plea for Methodical Reforms - Christian Ochsner; Christopher Zuber (Wirtschaftsdienst)
Abstract The cyclical adjustment procedure of the debt brake is one of the most important elements of the German deficit rule. The cyclical adjustment enables governments that are borrowing to take account of current business cycle developments: In economic upturns, the scope for net borrowing shrinks, and in downturns, it grows. Recently, various aspects of this procedure have been criticised. We argue that methodical reforms to the estimation procedure can reduce revisions and are better suited to quantify estimation uncertainty. However, revisions cannot be completely avoided. In our view, improving the estimation method with a lagged consideration of revisions seems appropriate for fiscal policy. In contrast, the technical component of the cyclical adjustment procedure should not be the starting point for a political reorientation of the German debt brake.